Faktor-faktor yang mempengaruhi niat untuk melakukan rasuah di kalangan penjawat awam pihak berkuasa tempatan / Enida Daud, Low Hock Heng and Ahmad Muhyuddin Hassan - Daud, Enida; Heng, Low Hock; Hassan, Ahmad Muhyuddin (2019)
This study is an attempt to examine the factors that influence the intention to commit corruption among public servants of the Local Authority in Johor. The public servants of Local Authority in Johor were selected as the unit analysis and the research instrument used were questionnaires. Data was analysed by using descriptive analysis Confirmatory Analysis Factor (CFA) and Structural Equation Modeling (SEM). The results of the descriptive analysis and the CFA found the intention to commit corruption was influenced by internal factors and external factors. The internal factors include neglecting religious values and demands, selfish attitudes, luxury lifestyle demands beyond their ability and greed. The identified external factors refer to the influence of family and colleagues, opportunities and spaces, unclear systems and procedures, social factors and modernization factors. The results of the hypothesis test found that internal factors and external factors have a significant influence on the intention to commit corruption.